Drinking water security for engineers, planners, and managers - Camarillo, Mary Kay; Jain, Ravi 1935-; Stringfellow, William T. (Integrated water security series, 2014)
"Concise and readable, Drinking Water Security for Engineers, Planners and Managers provides an overview of issues including infrastructure planning, planning to evaluate vulnerabilities and potential threats, capital improvement planning, and maintenance and risk management. This book also covers topics regarding potential contaminants, available water security technologies, analytical methods, and sensor technologies and networks. Other topics include transport and containment of contaminated water, treatment technologies and the treatability of contaminants ; Threat and vulnerability risk assessments and capital improvement ; Identification and characterization of potential contaminants and clean up ; Application of information assurance techniques to computerized systems"--Provided by publisher.